Continuous and Intermittent Alcohol Free-Choice from Pre-gestational Time to Lactation: Focus on Drinking Trajectories and Maternal Behavior - Brancato, Anna (Front Behav Neurosci, 2016)
Background: Alcohol consumption during pregnancy and lactation induces detrimental consequences, that are not limited to the direct in utero effects of the drug on fetuses, but extend to maternal care. However, the occurrence and severity of alcohol toxicity are related to the drinking pattern and the time of exposure. The present study investigated in female rats long-term alcohol drinking trajectories, by a continuous and intermittent free-choice paradigm, during pre-gestational time, pregnancy, and lactation; moreover, the consequences of long-term alcohol consumption on the response to natural reward and maternal behavior were evaluated. Methods: Virgin female rats were exposed to home-cage two-bottle continuous- or intermittent “alcohol (20% v/v) vs. water” choice regimen along 12 weeks and throughout pregnancy and lactation. Animals were tested for saccharin preference, and maternal behavior was assessed by recording dams' undisturbed spontaneous home-cage behavior in the presence of their offspring. Results: Our results show that the intermittent alcohol drinking-pattern induced an escalation in alcohol intake during pre-gestational time and lactation more than the continuous access, while a reduction in alcohol consumption was observed during pregnancy, contrarily to the drinking trajectories of the continuous access-exposed rats. Long-term voluntary alcohol intake induced a decreased saccharin preference in virgin female rats and a significant reduction in maternal care, with respect to control dams, although the intermittent drinking produced a greater impairment than the continuous-access paradigm. Conclusion: The present data indicate that both alcohol-drinking patterns are associated to modifications in the drinking trajectories of female rats, in pre-gestational time, during pregnancy and lactation. Moreover, long-lasting alcohol intake can affect sensitivity to natural rewarding stimuli and maternal behavior and sensitivity to natural rewarding stimuli in a pattern–related manner. This study underlies the importance of modeling human alcohol habit and its consequences on the mother-infant dyad, in order to prevent detrimental effects on offspring development and maturation.